Multidisciplinarity in Transition Pathways for Patients With Kidney Disease: The Current State of Play - Scarponi, Dorella; Cammaroto, Viviana; Pasini, Andrea; La Scola, Claudio; Mencarelli, Francesca; Bertulli, Cristina; Busutti, Marco; La Manna, Gaetano; Pession, Andrea (Frontiers in Pediatrics, 2021)
In the field of medical care, successful transition from pediatric-centred to adult-oriented healthcare provides a sense of continuity in the development of youth and prepares them to accept responsibility for and manage their own chronic kidney condition. This process requires the presence of a multidisciplinary team that acts as a bridge between child and adult services, involving family and caregivers, to ensure a comprehensive (clinical, cognitive, psychological, social) change for the young people. Although international guidelines agree on some important steps in the transition process, many differences can be observed between different countries. In Europe, the situation appears to be heterogeneous and, in some cases, quite disorganized as regards certain aspects: most centers do not use a written transition plan to outline their actions, or offer educational programmes; the timing of transfer to adult services is highly variable; the presence of a transition coordinator on the transition team is not necessarily seen; a dedicated off-site transition clinic is not always feasible in terms of costs and logistics. In the USA, the first standardized protocol for transition has recently been launched, which seems to have already achieved important positive, although limited, results. In Italy, the issue of transition is still in its infancy, however important efforts in the management of chronic diseases have already been initiated in some regions, and this gives us hope for the future of many young people.